Some Remarks Concerning the Embryos Bill of the Dutch Government - Eijk, Willem J. (Medicina e Morale, 2001)
After many years of delay the actual Dutch government has presented a detailed bill regarding embryo experiments, which has recently been passed by Parliament, but still has to be discussed in the senate. While permitting research with rest embryos for medical-biological ends, it forbids, albeit for the time being, creating embryos solely for the purpose of research. The bill includes, however, the possibility to decide after three to five years by Royal Decree that embryos may also be created only for scientific research. A few articles which will then be effective are already written into the bill. It has thus been stipulated beforehand the embryos especially created for scientific purposes may only be used for research concerning infertility, artificial reproduction, congenital abnormalities and transplant medicine. The government has proposed the permission of experiments with rest embryos and a temporary prohibitions of creating embryos solely for research taking into account four factors: respect for human life, the interest of medical science, the social acceptability of the creation for solely research in the Netherlands and that abroad. The original idea of possibly allowing after five to seven years the modification of the genetic material of the nucleus of germ cells has been abandoned in line with the 2001/20/EC European Directive regarding the mutual harmonisation of provisions concerning medical research. Room is however left for the 'in vitro nuclear transplantation' (or better cytoplasm transplantation) for the treatment of mitochondrial disorders. After that the creation of embryos for other purposes than pregnancy will have been allowed, cloning will be permitted for transplant medicine, but not for the production of a series of genetically identical individuals. The fusion of human and animal gametes is only permitted if the resulting being will not reach multicellular stage. According to the bill it is permitted to create chimeras by combining human with other human or animal embryos with a view to investigating human embryonal development, provided that the resulting chimera will not be kept alive longer than two weeks. The bill is here discussed from the perspective of catholic morla doctrine and international conventions.